Cost‐effectiveness of nurse‐led versus doctor‐led antiretroviral treatment in South Africa: pragmatic cluster randomised trial. Issue 6 (11th March 2013) - Barton, Garry R.; Fairall, Lara; Bachmann, Max O.; Uebel, Kerry; Timmerman, Venessa; Lombard, Carl; Zwarenstein, Merrick
Abstract: Objective: To estimate the cost‐effectiveness of nurse‐led versus doctor‐led antiretroviral treatment (ART) for HIV‐infected people. Design: Cost‐effectiveness analysis alongside a pragmatic cluster randomised controlled trial in 31 primary care clinics (16 intervention, 15 controls) in Free State Province, South Africa. Participants were HIV‐infected patients, aged ≥16 years. Cohort 1 (CD4 count ≤350 cells/μl, not yet receiving ART at enrolment): consisted of 5 390 intervention patients and 3 862 controls; Cohort 2 (already received ART for ≥6 months at enrolment) of 3 029 intervention patients and 3 202 controls. Nurses were authorised and trained to initiate and represcribe ART. Management and ART provision were decentralised to primary care clinics. In control clinics, doctors initiated and re‐prescribed ART, nurses monitored ART. Main outcome measure(s) were health service costs, death (cohort 1) and undetectable viral load (<400 copies/ml) (cohort 2) during the 12 months after enrolment. Results: For Cohort 1, the intervention had an estimated incremental cost of US102.52, an incremental effect of 0.42% fewer deaths and an incremental cost‐effectiveness ratio (ICER) of US24 500 per death averted. For Cohort 2, the intervention had an estimated incremental cost of US59.48, an incremental effect of 0.47% more undetectable viral loads and an ICER of US12 584 per undetectable viral load. Conclusions: Nurse‐led ART was associated with higher mean health service costs than doctor‐led care, with small effects on primary outcomes, and a high associated level of uncertainty. Given this, and the shortage of doctors, further implementation of nurse‐led ART should be considered, although this may increase health service costs.